Quaternary dating methods - Walker Mike (New Jersey John Wiley, 2005)
This introductory textbook introduces the basics of dating, the range of techniques available and the strengths and limitations of each of the principal methods.
Keywords: Geochronometry; Radioactive dating; Stratigraphic geology-Quaternary